Bus Superstructure Reinforcement for Safety Improvement against Rollover Accidents - Sandro Mihradi; Andhika Dhaniswara; Satrio Wicaksono; Andi Isra Mahyuddin (Journal of Engineering and Technological Sciences, 2022)
Bus rollover is considered the most dangerous road accident. To ensure bus safety against rollover accidents, the bus superstructure must conform to safety standards, one of which is UNR66. Unfortunately, in Indonesia, the increase in the number of buses has not been followed by bus safety improvement. In this paper, a numerical study on superstructure reinforcement to improve bus safety against rollover is presented. To reduce computational time, a simplified bus superstructure model comprising only three middle bays was used instead of a full bus model. Several superstructure reinforcements were implemented and their effectiveness in improving bus safety against rollover accidents was investigated. Among all reinforcements that were investigated, the most effective one was enhanced reinforcement by adding a connection between the seat structures and the side pillars. This modification yielded excellent results, as the modified superstructure showed a very significant improvement over a superstructure without reinforcement and it met the UNR66 residual space safety criterion.